Implementation of Public Policy for Electronic-Based Business Licensing Services at The Bangli Regency Investment Office and PTSP - Sri Irawati, Ni Luh Komang; Sudiarkajaya, I Made; Majuarsa , I Wayan (Al-Makki Publisher, 2025)
This study aims to analyze the implementation of electronic business licensing policies at the Bangli Regency Investment and One-Stop Integrated Services Office (DPMPTSP). This research focuses on three main aspects: the policy implementation process, the challenges faced, and the efforts made to improve the quality of business licensing services through the Online Single Submission – Risk Based Approach (OSS-RBA) system. This study uses a descriptive qualitative method, employing in-depth interviews, observations, and document analysis. The findings show that although the OSS-RBA policy has been implemented, it has not achieved optimal results. Key challenges include low digital literacy among the public, limited IT infrastructure, uneven technical capacity of human resources, and a lack of integration between national and regional licensing systems. In response, DPMPTSP Bangli has undertaken several initiatives, such as providing OSS assistance services, in-house technical training, and developing digital-based public communication. The study concludes that the successful implementation of OSS-RBA is highly dependent on technological readiness, bureaucratic competence, and effective inter-agency coordination.